Metal-based monatomic catalyst with adjustable site density as well as preparation method and application of metal-based monatomic catalyst
By loading cloth metal single atoms on a high-thermal stability support and performing high-temperature pyrolysis treatment, a metal-based single atom catalyst with adjustable site density was developed, which solved the problem of low activity of existing catalysts and achieved efficient and stable CO2 electrocatalysis Reduction reaction.
Patent Information
- Application Number
- CN202411755178.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-09-24
- Filing Date
- 2024-12-03
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-12-03
AI Technical Summary
The catalysts used in the existing CO2 electrocatalytic conversion have low catalytic activity and need to be improved to improve their activity and stability.
A metal-based single atom catalyst with adjustable site density was developed to regulate the site density and stability of the catalyst by loading cloth metal single atoms on a high-thermal stability support and by alkaline wet method and high-temperature pyrolysis treatment.
The high site density and stability of the catalyst are achieved, the adsorption amount of CO2 and the electron transfer rate are improved, the catalytic activity and product yield are enhanced, and the stability of the catalyst is improved. It is suitable for the reaction system for the preparation of methane by electrocatalytic reduction of CO2. .
Smart Images

Figure CN119465242A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrocatalytic carbon dioxide reduction, and in particular to a metal-based single-atom catalyst with adjustable site density, and a preparation method and application thereof. Background Art
[0002] Carbon dioxide (CO2) gas is an essential substance for human survival on Earth. However, human activities and industrial development have emitted a large amount of CO2 into the atmosphere, causing the atmospheric CO2 concentration to surge from 278ppm in the early 19th century to 421ppm in 2023, leading to a strong greenhouse effect and global climate problems. Therefore, reducing carbon emissions is urgent.
[0003] Several methods that have been put into practical use to achieve carbon neutrality include: carbon dioxide capture and storage technology (CCS) and carbon dioxide capture and conversion technology (CCU). Among them, the technology of using CO2 as raw material to produce high-value-added chemicals is one of the most attractive ways to reduce carbon emissions. Under mild reaction conditions, CO2 electrocatalytic conversion (ECR) technology can convert CO2 into high-value chemicals such as methane, ethanol, and ethylene. It can not only help reduce emissions and utilize resources, but also realize the conversion and storage of renewable energy into chemical energy. It is expected to become an important part of building a green and environmentally friendly new energy system. Through structural design and optimization to build efficient and stable catalysts, and integrating efficient and stable electrolytic cell systems, ECR technology is expected to develop into a carbon emission reduction method with practical commercial application value.
[0004] However, the catalysts currently used in CO2 electrocatalytic conversion still have the defect of low catalytic activity. Based on this, it is necessary to improve the current catalysts. Summary of the invention
[0005] The present invention aims to solve a problem in the related art at least to a certain extent, and provides a metal-based single-atom catalyst with adjustable site density, and a preparation method and application thereof.
[0006] In a first aspect, the present invention provides a metal-based single-atom catalyst with adjustable site density, comprising a heteroatom hybridized support and a metal, wherein the metal is supported on the support as a single-atom site;
[0007] The metal is coordinated to at least one of the heteroatoms;
[0008] The carrier is a carrier with high thermal stability, and the thermal decomposition loss of the carrier at a temperature of 300 to 1200° C. is 0.1 wt % to 90 wt %.
[0009] Preferably, the metal includes at least one of copper, cobalt, aluminum, iron, manganese, indium, nickel, tin, silver, palladium, platinum and gold;
[0010] And / or, the carrier includes at least one of a metal carrier, a metal oxide carrier, a metal carbide carrier, a metal nitride carrier, a metal phosphide carrier, a metal sulfide carrier, and a carbon carrier;
[0011] And / or, the heteroatom includes at least one of carbon, nitrogen, oxygen, sulfur, chlorine, and phosphorus.
[0012] Preferably, the site density of the metal is 1 to 256 / 25nm 2 ;
[0013] The metal carrier includes at least one of Pt, Au, Ag, Pd, and Rh;
[0014] The metal oxide carrier includes at least one of CeO2, Al2O3, Cr2O3, and TiO2;
[0015] The metal carbide carrier includes at least one of WC, VC, ZrC, TaC, SiC, and B4C;
[0016] The metal nitride carrier includes at least one of TaN and AlN;
[0017] The carbon carrier includes at least one of graphite, carbon nanotubes, graphyne, graphene, fullerene, and carbon particles.
[0018] In a second aspect, the present invention further provides a method for preparing the metal-based single-atom catalyst with adjustable site density, comprising the following steps:
[0019] adding the carrier to water and mixing to obtain a suspension;
[0020] Adding alkaline substances and organic solvents to the suspension, stirring, and obtaining a mixed solution;
[0021] Adding a mixed solution containing polymer monomers and metal salts into the mixed solution, reacting, separating the solid and the liquid, obtaining a precipitated product, and drying;
[0022] The dried precipitated product is mixed with carbon and nitrogen compounds and then pyrolyzed in an inert atmosphere to obtain a metal-based single-atom catalyst with adjustable site density;
[0023] The carrier is a carrier with high thermal stability, and the thermal decomposition loss of the carrier at a temperature of 300 to 1200° C. is 0.1 wt% to 90 wt%.
[0024] Preferably, before adding the carrier into the water, an organic solvent is added into the water, and the volume ratio of the organic solvent to water is (1-100):(1-3).
[0025] Preferably, the alkaline substance includes at least one of aqueous ammonia solution, sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, sodium hydroxide solution, potassium hydroxide solution, calcium hydroxide, and barium hydroxide;
[0026] and / or, the organic solvent comprises at least one of methanol, ethanol, glycerol, acetonitrile, acetone, chloroform, pyridine, N-methylpyrrolidone, and dimethylformamide;
[0027] And / or, the polymer monomer includes at least one of aniline monomers, pyrrole monomers, thiophene monomers, indole monomers, pyridine monomers, carbazole monomers, dopamine monomers, and p-phenylene vinylene monomers;
[0028] And / or, the metal salt includes at least one of a metal sulfate, a metal nitrate, a metal hypochlorite, a metal chlorate, a metal perchlorate, a metal fluoride, a metal acetate, a metal trifluoroacetate, a metal trifluoromethanesulfonate, a metal methanesulfonate, a metal p-toluenesulfonate, and a metal chloride;
[0029] The metal in the metal salt includes at least one of copper, cobalt, aluminum, iron, manganese, indium, nickel, tin, silver, palladium, platinum and gold;
[0030] And / or, the carbon-nitrogen compound includes at least one of urea, dicyandiamide, melamine, thiourea and amino acid.
[0031] Preferably, the pyrolysis temperature is 300-1200° C. and the time is 0.1-72 h.
[0032] Preferably, the concentration of the metal salt in the mixed solution containing the polymer monomer and the metal salt is 0.1 to 10 mg / mL;
[0033] and / or, the concentration of the polymer monomer in the mixed solution containing the polymer monomer and the metal salt is 10 to 30 mg / mL;
[0034] And / or, in the step of mixing the dried precipitated product with the carbon and nitrogen compound, the mass ratio of the dried precipitated product to the carbon and nitrogen compound is 1:(1-100).
[0035] Preferably, the pyrolysis comprises: mixing the dried precipitation product with the carbon and nitrogen compounds, firstly keeping the mixture at 0-40°C for 0.5-1h in an inert atmosphere, then heating the mixture to 300-1200°C at a rate of 1-50°C / min and keeping the mixture for 0.1-72h.
[0036] The inert atmosphere environment is an environment filled with inert gas, and the inert gas includes at least one of nitrogen, helium, neon, argon, krypton, and xenon.
[0037] Preferably, a mixed solution containing polymer monomers and metal salts is added to the mixed solution, and in the reaction step, the reaction temperature is 20 to 30° C. and the reaction time is 20 to 30 hours.
[0038] Preferably, the method comprises the following steps:
[0039] Adding a carrier and an organic solvent into water, mixing, and obtaining a suspension;
[0040] Adding alkaline substances and organic solvents to the suspension, stirring, and obtaining a mixed solution;
[0041] Adding a mixed solution containing polymer monomers and metal salts into the mixed solution, reacting, separating the solid and the liquid, obtaining a precipitated product, and drying;
[0042] The dried precipitated product is mixed with carbon and nitrogen compounds and then pyrolyzed in an inert atmosphere to obtain a metal-based single-atom catalyst with adjustable site density;
[0043] Wherein, the carrier is a graphite sheet, the metal salt is a copper salt, the polymer monomer is dopamine hydrochloride, and the alkaline substance is ammonia water; the mass concentration of the ammonia water is 25-32%;
[0044] The mixed solution is prepared by adding dopamine hydrochloride and copper salt into water to obtain a mixed solution;
[0045] In the step of adding a carrier and a first organic solvent to water, the mass ratio of the carrier, the organic solvent and the water is (0.05-0.2):(3-7):(40-50);
[0046] In the step of adding an alkaline substance and an organic solvent to the suspension, the mass ratio of the alkaline substance to the first organic solvent is (0.88-0.92):(14-18);
[0047] In the step of adding dopamine hydrochloride and copper salt to water, the mass ratio of dopamine hydrochloride, copper salt and water is (0.1-0.3):(0.02-0.08):(3-7);
[0048] The mass ratio of the carrier, the alkaline substance and dopamine hydrochloride is (0.05-0.2):(0.88-0.92):(0.1-0.3).
[0049] In a third aspect, the present invention also provides a gas diffusion electrode, comprising a substrate and a catalyst loaded on the substrate, wherein the catalyst is the metal-based single-atom catalyst with adjustable site density or the metal-based single-atom catalyst with adjustable site density prepared by the preparation method.
[0050] In a fourth aspect, the present invention also provides an application of the metal-based single-atom catalyst with adjustable site density, the metal-based single-atom catalyst with adjustable site density prepared by the preparation method, or the gas diffusion electrode in the CO2 electrocatalytic reduction reaction.
[0051] The metal-based single-atom catalyst with adjustable site density and its preparation method and application have the following beneficial effects compared with the prior art:
[0052] 1. The method for preparing a metal-based single-atom catalyst with adjustable site density of the present invention is to use an alkaline wet method, utilize the self-polymerization characteristics of phenolamine polymers under alkaline conditions, introduce a carrier with high thermal stability, change the self-polymerization form of the polymer, and then change the coordination density between the metal ion and the monomer on the polymer surface, so as to prepare a metal-based single-atom catalyst with adjustable site density and stability. The metal-based single-atom catalyst with adjustable site density is obtained by high-temperature pyrolysis treatment. During the pyrolysis process, the introduced carrier has high thermal stability, which helps to provide a more stable coordination environment for the metal single-atom site, so that the obtained metal single-atom catalyst has a higher site density and stability; while achieving similar catalytic effects, the amount of metal used is reduced; the high active metal site density increases the electron transfer rate and the adsorption amount of CO2 on the electrode surface, which is beneficial to improve the catalytic activity and product yield; secondly, the obtained metal active site has a higher oxidation state, which helps to reduce the adsorption energy of the intermediates generated in the catalytic process and promote CO2 methanation; finally, the more stable metal active site helps to improve the stability of the catalyst in the catalytic reaction;
[0053] 2. The method for preparing the metal-based single-atom catalyst with adjustable site density of the present invention has the characteristics of simple preparation, low price, environmental friendliness, high efficiency and stability, and has the prospect of large-scale industrial application.
[0054] 3. The metal-based single-atom catalyst with adjustable site density prepared by the present invention can be applied to the reaction system of CO2 electrocatalytic reduction to CH4. The high active metal site density can increase the electron transfer rate and the adsorption amount of CO2 on the electrode surface, while the high oxidation state of the metal active site helps to reduce the adsorption energy of the intermediates generated in the catalytic process, inhibit carbon-carbon coupling, and improve the selectivity of CO2 reduction to CH4. The more stable metal active sites improve the stability of the catalyst in the catalytic reaction, thereby realizing efficient and stable circular economic utilization and conversion of carbon dioxide. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art descriptions. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0056] Figure 1 This is a schematic flow chart of a method for preparing a metal-based single-atom catalyst with adjustable site density according to the present invention;
[0057] Figure 2 ad are scanning transmission electron microscopy images of Cu single atom catalysts prepared in Examples 1 to 4, respectively; Figure 2 eh are scanning transmission electron microscopy images of Cu single atom catalysts prepared in Comparative Examples 1 to 4, respectively;
[0058] Figure 3 The site spacing d of the Cu single atom catalysts prepared in Examples 1 to 4 and Comparative Examples 1 to 4 is site value;
[0059] Figure 4 where n is the site density n of the Cu single atom catalysts prepared in Examples 1 to 4 and Comparative Examples 1 to 4. s (Cuatom 100nm -2 );
[0060] Figure 5 The Faraday efficiency diagram of the gas diffusion electrodes prepared in Examples 1 to 4 and Comparative Examples 1 to 4 for reducing CH4 at different potentials. DETAILED DESCRIPTION
[0061] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0062] It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may be in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the numbered ranges, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated in this article, it is meant to include any cited numbers (fractions or integers) within the indicated range.
[0063] The embodiment of the present application provides a metal-based single-atom catalyst with adjustable site density, including a heteroatom hybridized carrier and a metal, wherein the metal is loaded on the carrier as a single-atom site;
[0064] The metal is coordinated to at least one of the heteroatoms;
[0065] The carrier is a carrier with high thermal stability, and the thermal decomposition loss of the carrier at a temperature of 300 to 1200 DEG C is 0.1 wt% to 90 wt%.
[0066] In some embodiments, the metal includes at least one of copper, cobalt, aluminum, iron, manganese, indium, nickel, tin, silver, palladium, platinum, and gold.
[0067] In some embodiments, the support includes at least one of a metal support, a metal oxide support, a metal carbide support, a metal nitride support, a metal phosphide support, a metal sulfide support, and a carbon support.
[0068] Preferably, the metal support comprises at least one of Pt, Au, Ag, Pd, and Rh;
[0069] The metal oxide carrier includes at least one of CeO2, Al2O3, Cr2O3, and TiO2;
[0070] The metal carbide carrier includes at least one of WC, VC, ZrC, TaC, SiC, and B4C;
[0071] The metal nitride carrier includes at least one of TaN and AlN;
[0072] The carbon carrier includes at least one of graphite, carbon nanotubes, graphyne, graphene, fullerene, and carbon particles.
[0073] In some embodiments, the heteroatom includes at least one of carbon, nitrogen, oxygen, sulfur, chlorine, and phosphorus.
[0074] In some embodiments, the metal site density is 1 to 256 / 25nm. 2 .
[0075] Based on the same inventive concept, the present invention also provides a method for preparing a metal-based single-atom catalyst with adjustable site density, such as Figure 1 As shown, the following steps are included:
[0076] S1, adding the carrier to water, mixing, and obtaining a suspension;
[0077] S2, adding the alkaline substance and the organic solvent to the suspension, stirring to obtain a mixed solution;
[0078] S3, adding a mixed solution containing polymer monomers and metal salts into the mixed solution, reacting, separating the solid and the liquid, obtaining a precipitated product, and drying;
[0079] S4, mixing the dried precipitated product with a carbon-nitrogen compound and pyrolyzing the mixture under an inert atmosphere to obtain a metal-based single-atom catalyst with adjustable site density;
[0080] The carrier is a carrier with high thermal stability, and the thermal decomposition loss of the carrier at a temperature of 300 to 1200° C. is 0.1 wt% to 90 wt%.
[0081] The method for preparing a metal-based single-atom catalyst with adjustable site density of the present invention utilizes the self-polymerization characteristics of phenolamine polymers under alkaline conditions through an alkaline wet method, introduces a carrier with high thermal stability, changes the self-polymerization form of the polymer, and then changes the coordination density between metal ions and monomers on the surface of the polymer, thereby preparing a metal-based single-atom catalyst with adjustable site density and stability. The metal-based single-atom catalyst with adjustable site density is obtained by high-temperature pyrolysis treatment. During the pyrolysis process, the introduced carrier has high thermal stability, which helps to provide a more stable coordination environment for the metal single-atom site, so that the obtained metal single-atom catalyst has a higher site density and stability; while achieving similar catalytic effects, the amount of metal used is reduced; the high active metal site density increases the electron transfer rate and the adsorption amount of CO2 on the electrode surface, which is beneficial to improving the catalytic activity and product yield; secondly, the obtained metal active site has a higher oxidation state, which helps to reduce the adsorption energy of the intermediate generated in the catalytic process and promote CO2 methanation; finally, the more stable metal active site helps to improve the stability of the catalyst in the catalytic reaction. The metal-based single-atom catalyst with adjustable site density prepared by the present invention exhibits significant activity, methane selectivity and stability in the electrocatalytic carbon dioxide methanation reaction. The catalyst is suitable for replacing the high-temperature driven Sabatier reaction and can also be used in the field of carbon emission reduction.
[0082] In addition, the method for preparing the metal-based single-atom catalyst with adjustable site density in the present invention has the characteristics of simple preparation, low price, environmental friendliness, high efficiency and stability, and has the prospect of large-scale industrial application.
[0083] In some embodiments, in the above step S1, the carrier is added to water and mixed to obtain a suspension, which is recorded as system I. In this embodiment, the carrier has high thermal stability, and the pyrolysis loss of the carrier at a temperature of 300° C. to 1200° C. is 0.01wt% to 90wt%, preferably 5.0wt% to 30wt%. The length of the carrier is 0.1μm to 100μm, and the thickness is 1.0nm to 1.0μm.
[0084] The carrier provided in this embodiment has high thermal stability, which helps to provide a more stable coordination environment for the metal single atom sites, so that the obtained metal single atom catalyst has higher site density and stability.
[0085] In some embodiments, before adding the carrier into water, the process further includes adding an organic solvent into the water, wherein the volume ratio of the organic solvent to water is (1-100):(1-3).
[0086] In some embodiments, the carrier is added to water and mixed, and the mixing step is one or more of stirring, ultrasonication, rotation, shaking, tapping, and vibration.
[0087] Specifically, in the above step S2, the alkaline substance and the organic solvent are added to the system I in step S1, stirred, and a mixed solution is obtained, which is recorded as system II.
[0088] In some embodiments, the alkaline substance includes at least one of aqueous ammonia solution, sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, sodium hydroxide solution, potassium hydroxide solution, calcium hydroxide, and barium hydroxide.
[0089] In some embodiments, the organic solvent includes at least one of methanol, ethanol, glycerol, acetonitrile, acetone, chloroform, pyridine, N-methylpyrrolidone, and dimethylformamide.
[0090] In some embodiments, the alkaline substance and the organic solvent are added to the system I in step S1 and stirred; wherein, in the stirring step, the rotation speed is 60 to 3000 r / min and the time is 0.5 to 120 h.
[0091] In some embodiments, in the above step S3, a mixed solution containing polymer monomers and metal salts is added to the system II of step S2 to react to obtain a uniformly dispersed solution, which is recorded as system III. System III is centrifuged to obtain a precipitated product, and the precipitated product is transferred to an inert atmosphere environment or dried under vacuum conditions.
[0092] In some embodiments, a mixed solution containing a polymer monomer and a metal salt is added to the mixed solution for reaction; wherein the reaction temperature is 20 to 30° C. and the reaction time is 20 to 30 hours.
[0093] In some embodiments, the polymer monomer includes at least one of aniline monomers, pyrrole monomers, thiophene monomers, indole monomers, pyridine monomers, carbazole monomers, dopamine monomers, and p-phenylene vinylene monomers; preferably, the polymer monomer is a dopamine monomer, more preferably dopamine hydrochloride.
[0094] In some embodiments, the metal salt includes at least one of metal sulfate salts, metal nitrate salts, metal hypochlorite salts, metal chlorate salts, metal perchlorate salts, metal fluoride salts, metal acetate salts, metal trifluoroacetate salts, metal trifluoromethanesulfonate salts, metal methanesulfonate salts, metal p-toluenesulfonate salts, and metal chloride salts; the metal in the metal salt includes at least one of copper, cobalt, aluminum, iron, manganese, indium, nickel, tin, silver, palladium, platinum, and gold.
[0095] In some embodiments, the concentration of the metal salt in the mixed solution containing the polymer monomer and the metal salt is 0.1-10 mg / mL.
[0096] In some embodiments, the concentration of the polymer monomer in the mixed solution containing the polymer monomer and the metal salt is 10-30 mg / mL.
[0097] In some embodiments, a mixed solution containing polymer monomers and metal salts is slowly added into system II at a dropping speed of 0.5 mL / min to 60 mL / min.
[0098] In some embodiments, the system III is centrifuged to obtain a precipitated product, and the precipitated product is transferred to an inert atmosphere environment or dried under vacuum conditions; wherein, in the centrifugation step, the rotation speed is 1000 to 30000 r / min, and the time is 0.1 h to 1.0 h; the inert atmosphere environment is an environment filled with inert gas, and the inert gas includes one or more of nitrogen, helium, neon, argon, krypton, and xenon; the purity of the inert gas is 90.0% to 99.999%, and the flow rate is 5 to 10 3 sccm (standard milliliters per minute); the drying step includes one or more of heating, inert gas washing, and vacuum drying; the heating range is 0 to 150°C, the time is 0.1h to 24h, and the heating rate is 1 to 50°C / min; the inert gas washing rate is 10cm 3 / min~1000cm 3 / min.
[0099] In some embodiments, in the above step S4, the dried precipitated product is mixed and ground with a carbon nitrogen compound, and finally the evenly ground powder sample is loaded into a quartz crucible, and the crucible is transferred to a tubular furnace under an inert atmosphere for a temperature-increasing pyrolysis treatment. After the pyrolysis treatment, it is naturally cooled to room temperature (25°C) to obtain a metal-based single-atom catalyst with adjustable site density; the mass of the powder sample loaded in the quartz crucible is 0.01g to 1.0kg.
[0100] In some embodiments, the carbon-nitrogen compound comprises at least one of urea, dicyandiamide, melamine, thiourea, and amino acid. Preferably, the carbon-nitrogen compound is dicyandiamide.
[0101] Specifically, the above carbon-nitrogen compounds provide a material basis for N doping.
[0102] In some embodiments, the dried precipitated product is mixed with a carbonitride and ground at a grinding speed of 1 to 1000 r / min for a grinding time of 0.1 to 1.0 h.
[0103] In some embodiments, in the step of mixing the dried precipitated product with the carbon-nitrogen compound, the mass ratio of the dried precipitated product to the carbon-nitrogen compound is 1:(1-100).
[0104] In some embodiments, a tubular furnace is used for the pyrolysis treatment. Specifically, the pyrolysis temperature is 300 to 1200° C. and the time is 0.1 to 72 hours.
[0105] In some embodiments, pyrolysis includes one or more of normal temperature maintenance, heating, and constant temperature; the normal temperature is 0-40°C; the heating range is 0-1200°C, preferably 300-1200°C, the heating time is 0.3-72h, and the heating rate is 1-50°C / min; the constant temperature range is 0-1200°C, preferably 300-1200°C, and the constant temperature time is 0.1-72h.
[0106] In some embodiments, pyrolysis includes mixing the dried precipitated product with carbon-nitrogen compounds in an inert atmosphere, first keeping the mixture at 0-40°C for 0.5-1h, then heating the mixture to 300-1200°C at a rate of 1-50°C / min and keeping the mixture for 0.1-72h; the inert atmosphere is an environment filled with inert gas, and the inert gas includes at least one of nitrogen, helium, neon, argon, krypton, and xenon.
[0107] In some embodiments, a method for preparing a metal-based single-atom catalyst with adjustable site density comprises the following steps:
[0108] S1, adding a carrier and an organic solvent into water, mixing, and obtaining a suspension;
[0109] S2, adding the alkaline substance and the organic solvent to the suspension, stirring to obtain a mixed solution;
[0110] S3, adding a mixed solution containing polymer monomers and metal salts into the mixed solution, reacting, separating the solid and the liquid, obtaining a precipitated product, and drying;
[0111] S4, mixing the dried precipitated product with a carbon-nitrogen compound and pyrolyzing the mixture under an inert atmosphere to obtain a metal-based single-atom catalyst with adjustable site density;
[0112] The carrier is graphite, the metal salt is copper salt, the polymer monomer is dopamine hydrochloride, and the alkaline substance is ammonia water; the mass concentration of the ammonia water is 25-32%;
[0113] The mixed solution is prepared by adding dopamine hydrochloride and copper salt into water to obtain a mixed solution;
[0114] In the step of adding the carrier and the first organic solvent to water, the mass ratio of the carrier, the organic solvent and the water is (0.05-0.2):(3-7):(40-50);
[0115] In the step of adding the alkaline substance and the organic solvent to the suspension, the mass ratio of the alkaline substance to the first organic solvent is (0.88-0.92):(14-18);
[0116] In the step of adding dopamine hydrochloride and copper salt to water, the mass ratio of dopamine hydrochloride, copper salt (preferably copper sulfate) and water is (0.1-0.3):(0.02-0.08):(3-7);
[0117] The mass ratio of the carrier, the alkaline substance and dopamine hydrochloride is (0.05-0.2):(0.88-0.92):(0.1-0.3).
[0118] In the above embodiment, if the polymer monomer is dopamine hydrochloride, a mixed solution containing the polymer monomer and the metal salt is added to the mixed solution to induce rapid self-polymerization of dopamine into polydopamine. At the same time, polydopamine and metal ions undergo an in-situ coordination reaction.
[0119] Based on the same inventive concept, the present invention also provides a gas diffusion electrode, comprising a substrate and a catalyst loaded on the substrate, wherein the catalyst is the above-mentioned metal-based single-atom catalyst with adjustable site density or the metal-based single-atom catalyst with adjustable site density prepared by the above-mentioned preparation method.
[0120] The preparation method of the gas diffusion electrode comprises: adding the metal-based single-atom catalyst with adjustable site density into an organic solvent to prepare a catalyst slurry, coating the catalyst slurry on the surface of a substrate, and drying to obtain a gas diffusion electrode.
[0121] In some embodiments, the substrate is a carbon-based gas diffusion layer, and the organic solvent includes isopropanol, etc.; specifically, 0.1-0.3 g of a metal-based single-atom catalyst with adjustable site density and 80-120 μL of Nafion solution (perfluorosulfonic acid polymer solution, concentration of 5 wt%) are added to 0.5-2 mL of isopropanol, and ultrasonicated for 15 minutes to obtain a catalyst slurry; the catalyst slurry is drop-coated on the surface of the carbon-based gas diffusion layer and dried to obtain a gas diffusion electrode.
[0122] Based on the same inventive concept, the present invention also provides an application of the above-mentioned metal-based single-atom catalyst with adjustable site density or the metal-based single-atom catalyst with adjustable site density prepared by the above-mentioned preparation method or the above-mentioned gas diffusion electrode in CO2 electrocatalytic reduction reaction.
[0123] The metal-based single-atom catalyst with adjustable site density prepared by the present invention can be applied to the reaction system of CO2 electrocatalytic reduction to CH4. The high active metal site density can increase the electron transfer rate and the adsorption amount of CO2 on the electrode surface, while the high oxidation state of the metal active site helps to reduce the adsorption energy of the intermediates generated in the catalytic process, inhibit carbon-carbon coupling, and improve the selectivity of CO2 reduction to CH4. The more stable metal active site improves the stability of the catalyst in the catalytic reaction, thereby realizing efficient and stable circular economic utilization and conversion of carbon dioxide.
[0124] The following further illustrates the metal-based single-atom catalyst with adjustable site density and its preparation method and application with specific examples. This section further illustrates the content of the present invention in conjunction with specific examples, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0125] Example 1
[0126] The present application embodiment provides a metal-based single-atom catalyst with adjustable site density, comprising the following steps:
[0127] S1. Add 0.1 g of graphite (purchased from Merck, Germany, powder, particle size <45 μm, ≥99.99%) and 5 mL of ethanol (mass: 3.9465 g) to 45 mL of water (mass: 45 g), and ultrasonicate for 30 min to obtain a suspension;
[0128] S2, adding 1 mL of aqueous ammonia (mass concentration of 30%, mass of 0.892 g) and 20 mL of ethanol (mass of 15.786 g) to the suspension in step S1, stirring to obtain a mixed solution;
[0129] S3, adding 0.125g dopamine hydrochloride powder and 0.02g anhydrous copper sulfate powder to 5mL water (mass 5g), stirring and mixing to obtain a mixed solution containing polymer monomers and metal salts;
[0130] The mixed solution containing the polymer monomer and the metal salt is added dropwise to the mixed solution in step S2 to react (initiating rapid self-polymerization of dopamine into polydopamine, and at the same time, polydopamine and metal ions undergo in-situ coordination reaction); wherein the reaction temperature is 25° C., the reaction time is 24 hours, and a polydopamine-copper polymer precursor is prepared, which is marked as PDA-Cu-40 polymer precursor;
[0131] S4, collecting the PDA-Cu-40 polymer precursor in step S3 by centrifugation, transferring it to a vacuum drying oven, and subjecting it to vacuum drying at 60° C.;
[0132] S5, mixing the PDA-Cu-40 polymer precursor dried in step S4 with dicyandiamide powder in a mass ratio of 1:11 and grinding for 10 minutes to obtain a uniformly ground powder, which is labeled as PDA-Cu-40-DCD; then transferring 0.3 g of the uniformly ground PDA-Cu-40-DCD powder to a quartz boat;
[0133] S6. Transfer the quartz boat containing PDA-Cu-40-DCD powder to a tubular furnace for heating pyrolysis treatment; the pyrolysis treatment is specifically as follows: in an argon atmosphere (during the entire pyrolysis process, argon gas at a flow rate of 50 sccm is introduced into the tubular furnace), maintain a constant temperature at 25°C for 1 hour, then increase the temperature from 25°C to 800°C at a rate of 5°C / min, then keep it at 800°C for 1.5 hours, and finally cool naturally to room temperature (25°C); the sample obtained after pyrolysis is a Cu single-atom catalyst, marked as CuNG1.
[0134] This embodiment also provides a method for preparing a gas diffusion electrode, comprising the following steps:
[0135] The CuNG1 prepared in Example 1 and 100 μL Nafion solution (concentration of 5 wt%) were added to 1 mL of isopropanol and ultrasonicated for 15 min to obtain a catalyst slurry; the catalyst slurry was drop-coated on the surface of the carbon-based gas diffusion layer and dried to obtain a catalyst loading of 0.5 mg / cm 2 The gas diffusion electrode is labeled as CuNG1 / GDL gas diffusion electrode.
[0136] Example 2
[0137] The present application embodiment provides a metal-based single-atom catalyst with adjustable site density, comprising the following steps:
[0138] S1. Add 0.1 g of graphite (purchased from Merck, Germany, powder, particle size <45 μm, ≥99.99%) and 5 mL of ethanol (mass: 3.9465 g) to 45 mL of water (mass: 45 g), and ultrasonicate for 30 min to obtain a suspension;
[0139] S2, adding 1 mL of aqueous ammonia (mass concentration of 30%, mass of 0.892 g) and 20 mL of ethanol (mass of 15.786 g) to the suspension in step S1, stirring to obtain a mixed solution;
[0140] S3, adding 0.125g dopamine hydrochloride powder and 0.04g anhydrous copper sulfate powder to 5mL water (mass 5g), stirring and mixing to obtain a mixed solution containing polymer monomers and metal salts;
[0141] The mixed solution containing the polymer monomer and the metal salt is added dropwise to the mixed solution in step S2 to react (initiating rapid self-polymerization of dopamine into polydopamine, and at the same time, polydopamine and metal ions undergo in-situ coordination reaction); wherein the reaction temperature is 25° C., the reaction time is 24 hours, and a polydopamine-copper polymer precursor is prepared, which is marked as PDA-Cu-80 polymer precursor;
[0142] S4, collecting the PDA-Cu-80 polymer precursor in step S3 by centrifugation, transferring it to a vacuum drying oven, and vacuum drying it at 60° C.;
[0143] S5, mixing the PDA-Cu-80 polymer precursor dried in step S4 with dicyandiamide powder in a mass ratio of 1:11 and grinding for 10 minutes to obtain a uniformly ground powder, which is labeled as PDA-Cu-80-DCD; then transferring 0.3 g of the uniformly ground PDA-Cu-80-DCD powder to a quartz boat;
[0144] S6. Transfer the quartz boat containing PDA-Cu-80-DCD powder to a tubular furnace for heating pyrolysis treatment; the pyrolysis treatment is specifically as follows: in an argon atmosphere (during the entire pyrolysis process, argon is introduced into the tubular furnace at a flow rate of 50 sccm), maintain a constant temperature at 25°C for 1 hour, then increase the temperature from 25°C to 800°C at a rate of 5°C / min, then keep it at 800°C for 1.5 hours, and finally cool naturally to room temperature (25°C); the sample obtained after pyrolysis is a Cu single-atom catalyst, marked as CuNG2.
[0145] This embodiment also provides a method for preparing a gas diffusion electrode, comprising the following steps:
[0146] The CuNG2 prepared in Example 2 and 100 μL Nafion solution (concentration of 5 wt%) were added to 1 mL of isopropanol and ultrasonicated for 15 min to obtain a catalyst slurry. The catalyst slurry was drop-coated on the surface of the carbon-based gas diffusion layer and dried to obtain a catalyst loading of 0.5 mg / cm 2 The gas diffusion electrode is labeled as CuNG1 / GDL gas diffusion electrode.
[0147] Example 3
[0148] The present application embodiment provides a metal-based single-atom catalyst with adjustable site density, comprising the following steps:
[0149] S1. Add 0.1 g of graphite (purchased from Merck, Germany, powder, particle size <45 μm, ≥99.99%) and 5 mL of ethanol (mass: 3.9465 g) to 45 mL of water (mass: 45 g), and ultrasonicate for 30 min to obtain a suspension;
[0150] S2, adding 1 mL of aqueous ammonia (mass concentration of 30%, mass of 0.892 g) and 20 mL of ethanol (mass of 15.786 g) to the suspension in step S1, stirring to obtain a mixed solution;
[0151] S3, adding 0.125g dopamine hydrochloride powder and 0.05g anhydrous copper sulfate powder to 5mL water (mass 5g), stirring and mixing to obtain a mixed solution containing polymer monomers and metal salts;
[0152] The mixed solution containing the polymer monomer and the metal salt is added dropwise to the mixed solution in step S2 to react (initiating rapid self-polymerization of dopamine into polydopamine, and at the same time, polydopamine and metal ions undergo in-situ coordination reaction); wherein the reaction temperature is 25° C., the reaction time is 24 hours, and a polydopamine-copper polymer precursor is prepared, which is marked as PDA-Cu-100 polymer precursor;
[0153] S4, collecting the PDA-Cu-100 polymer precursor in step S3 by centrifugation, transferring it to a vacuum drying oven, and subjecting it to vacuum drying at 60° C.;
[0154] S5, mixing the PDA-Cu-100 polymer precursor dried in step S4 with dicyandiamide powder in a mass ratio of 1:11 and grinding for 10 minutes to obtain a uniformly ground powder, which is labeled as PDA-Cu-100-DCD; then transferring 0.3 g of the uniformly ground PDA-Cu-100-DCD powder to a quartz boat;
[0155] S6. Transfer the quartz boat carrying PDA-Cu-100-DCD powder to a tubular furnace for heating pyrolysis treatment; the pyrolysis treatment is specifically as follows: in an argon atmosphere (during the entire pyrolysis process, argon is introduced into the tubular furnace at a flow rate of 50 sccm), maintain a constant temperature at 25°C for 1 hour, then increase the temperature from 25°C to 800°C at a rate of 5°C / min, then keep it at 800°C for 1.5 hours, and finally cool naturally to room temperature (25°C); the sample obtained after pyrolysis is a Cu single-atom catalyst, marked as CuNG3.
[0156] This embodiment also provides a method for preparing a gas diffusion electrode, comprising the following steps:
[0157] The CuNG3 prepared in Example 3 and 100 μL Nafion solution (concentration of 5 wt%) were added to 1 mL of isopropanol and ultrasonicated for 15 min to obtain a catalyst slurry. The catalyst slurry was drop-coated on the surface of the carbon-based gas diffusion layer and dried to obtain a catalyst loading of 0.5 mg / cm 2 The gas diffusion electrode is labeled as CuNG1 / GDL gas diffusion electrode.
[0158] Example 4
[0159] The present application embodiment provides a metal-based single-atom catalyst with adjustable site density, comprising the following steps:
[0160] S1. Add 0.1 g of graphite (purchased from Merck, Germany, powder, particle size <45 μm, ≥99.99%) and 5 mL of ethanol (mass: 3.9465 g) to 45 mL of water (mass: 45 g), and ultrasonicate for 30 min to obtain a suspension;
[0161] S2, adding 1 mL of aqueous ammonia (mass concentration of 30%, mass of 0.892 g) and 20 mL of ethanol (mass of 15.786 g) to the suspension in step S1, stirring to obtain a mixed solution;
[0162] S3, adding 0.125g dopamine hydrochloride powder and 0.08g anhydrous copper sulfate powder to 5mL water (mass 5g), stirring and mixing to obtain a mixed solution containing polymer monomers and metal salts;
[0163] The mixed solution containing the polymer monomer and the metal salt is added dropwise to the mixed solution in step S2 to react (initiating rapid self-polymerization of dopamine into polydopamine, and at the same time, polydopamine and metal ions undergo in-situ coordination reaction); wherein the reaction temperature is 25° C. and the reaction time is 24 hours to prepare a polydopamine-copper polymer precursor, which is labeled as PDA-Cu-160 polymer precursor;
[0164] S4, collecting the PDA-Cu-160 polymer precursor in step S3 by centrifugation, transferring it to a vacuum drying oven, and vacuum drying it at 60° C.;
[0165] S5, mixing the PDA-Cu-160 polymer precursor dried in step S4 with dicyandiamide powder in a mass ratio of 1:11 and grinding for 10 minutes to obtain a uniformly ground powder, which is labeled as PDA-Cu-160-DCD; then transferring 0.3 g of the uniformly ground PDA-Cu-160-DCD powder to a quartz boat;
[0166] S6. Transfer the quartz boat carrying PDA-Cu-160-DCD powder to a tubular furnace for heating pyrolysis treatment; the pyrolysis treatment is specifically as follows: in an argon atmosphere (during the entire pyrolysis process, argon gas with a flow rate of 50 sccm is introduced into the tubular furnace), maintain a constant temperature at 25°C for 1 hour, then increase the temperature from 25°C to 800°C at a rate of 5°C / min, then keep it at 800°C for 1.5 hours, and finally cool naturally to room temperature (25°C); the sample obtained after pyrolysis is a Cu single-atom catalyst, marked as CuNG4.
[0167] This embodiment also provides a method for preparing a gas diffusion electrode, comprising the following steps:
[0168] The CuNG4 prepared in Example 4 and 100 μL Nafion solution (concentration of 5 wt%) were added to 1 mL of isopropanol and ultrasonicated for 15 min to obtain a catalyst slurry. The catalyst slurry was drop-coated on the surface of the carbon-based gas diffusion layer and dried to obtain a catalyst loading of 0.5 mg / cm 2 The gas diffusion electrode is labeled as CuNG1 / GDL gas diffusion electrode.
[0169] Comparative Example 1
[0170] This comparative example provides a metal-based single-atom catalyst with adjustable site density, comprising the following steps:
[0171] S1. Mix and stir 1 mL of aqueous ammonia (mass concentration of 30%, mass of 0.892 g), 20 mL of ethanol (mass of 15.786 g), and 45 mL of water (mass of 45 g) to obtain a mixed solution;
[0172] S2, adding 0.125g dopamine hydrochloride powder and 0.02g anhydrous copper sulfate powder to 5mL water (mass 5g), stirring and mixing to obtain a mixed solution containing polymer monomers and metal salts;
[0173] The mixed solution containing the polymer monomer and the metal salt is added dropwise to the mixed solution in step S1 to react (initiating rapid self-polymerization of dopamine into polydopamine, and at the same time, polydopamine and metal ions undergo in-situ coordination reaction); wherein the reaction temperature is 25° C., the reaction time is 24 hours, and a polydopamine-copper polymer precursor is prepared, which is marked as PDA-Cu-C40 polymer precursor;
[0174] S3, collecting the PDA-Cu-C40 polymer precursor in step S2 by centrifugation, transferring it to a vacuum drying oven, and vacuum drying it at 60° C.;
[0175] S4, mixing the PDA-Cu-C40 polymer precursor dried in step S3 with dicyandiamide powder in a mass ratio of 1:11 and grinding for 10 minutes to obtain a uniformly ground powder, which is labeled as PDA-Cu-C40-DCD; then transferring 0.3 g of the uniformly ground PDA-Cu-C40-DCD powder to a quartz boat;
[0176] S5. The quartz boat carrying the PDA-Cu-C40-DCD powder was transferred to a tubular furnace for heating pyrolysis treatment. The pyrolysis treatment was specifically as follows: in an argon atmosphere (during the entire pyrolysis process, argon was introduced into the tubular furnace at a flow rate of 50 sccm), the temperature was maintained at 25°C for 1 hour, then the temperature was increased from 25°C to 800°C at a rate of 5°C / min, and then kept at 800°C for 1.5 hours, and finally naturally cooled to room temperature (25°C); the sample obtained after pyrolysis was a Cu single-atom catalyst, marked as CuNC1.
[0177] This comparative example also provides a method for preparing a gas diffusion electrode, comprising the following steps:
[0178] The CuNC1 prepared in Comparative Example 1 and 100 μL Nafion solution (concentration of 5 wt%) were added to 1 mL of isopropanol and ultrasonicated for 15 min to obtain a catalyst slurry; the catalyst slurry was drop-coated on the surface of the carbon-based gas diffusion layer and dried to obtain a catalyst loading of 0.5 mg / cm 2 The gas diffusion electrode is labeled as CuNC1 / GDL gas diffusion electrode.
[0179] Comparative Example 2
[0180] This comparative example provides a metal-based single-atom catalyst with adjustable site density, comprising the following steps:
[0181] S1. Mix and stir 1 mL of aqueous ammonia (mass concentration of 30%, mass of 0.892 g), 20 mL of ethanol (mass of 15.786 g), and 45 mL of water (mass of 45 g) to obtain a mixed solution;
[0182] S2, adding 0.125g dopamine hydrochloride powder and 0.04g anhydrous copper sulfate powder to 5mL water (mass 5g), stirring and mixing to obtain a mixed solution containing polymer monomers and metal salts;
[0183] The mixed solution containing the polymer monomer and the metal salt is added dropwise to the mixed solution in step S1 to react (initiating rapid self-polymerization of dopamine into polydopamine, and at the same time, polydopamine and metal ions undergo in-situ coordination reaction); wherein the reaction temperature is 25° C., the reaction time is 24 hours, and a polydopamine-copper polymer precursor is prepared, which is marked as PDA-Cu-C80 polymer precursor;
[0184] S3, collecting the PDA-Cu-C80 polymer precursor in step S2 by centrifugation, transferring it to a vacuum drying oven, and vacuum drying it at 60° C.;
[0185] S4, the PDA-Cu-C80 polymer precursor dried in step S3 and the dicyandiamide powder were mixed in a mass ratio of 1:11 and ground for 10 minutes to obtain a uniformly ground powder, which was labeled as PDA-Cu-C80-DCD; then 0.3 g of the uniformly ground PDA-Cu-C80-DCD powder was transferred to a quartz boat;
[0186] S5. Transfer the quartz boat carrying PDA-Cu-C80-DCD powder to a tubular furnace for heating pyrolysis treatment; the pyrolysis treatment is specifically as follows: in an argon atmosphere (during the entire pyrolysis process, argon gas with a flow rate of 50 sccm is introduced into the tubular furnace), maintain a constant temperature at 25°C for 1 hour, then increase the temperature from 25°C to 800°C at a rate of 5°C / min, then keep it at 800°C for 1.5 hours, and finally cool naturally to room temperature (25°C); the sample obtained after pyrolysis is a Cu single-atom catalyst, marked as CuNC2.
[0187] This comparative example also provides a method for preparing a gas diffusion electrode, comprising the following steps:
[0188] The CuNC2 prepared in Comparative Example 2 and 100 μL Nafion solution (concentration of 5 wt%) were added to 1 mL of isopropanol and ultrasonicated for 15 min to obtain a catalyst slurry; the catalyst slurry was drop-coated on the surface of the carbon-based gas diffusion layer and dried to obtain a catalyst loading of 0.5 mg / cm 2 The gas diffusion electrode is labeled as CuNC2 / GDL gas diffusion electrode.
[0189] Comparative Example 3
[0190] This comparative example provides a metal-based single-atom catalyst with adjustable site density, comprising the following steps:
[0191] S1. Mix and stir 1 mL of aqueous ammonia (mass concentration of 30%, mass of 0.892 g), 20 mL of ethanol (mass of 15.786 g), and 45 mL of water (mass of 45 g) to obtain a mixed solution;
[0192] S2, adding 0.125g dopamine hydrochloride powder and 0.05g anhydrous copper sulfate powder to 5mL water (mass 5g), stirring and mixing to obtain a mixed solution containing polymer monomers and metal salts;
[0193] The mixed solution containing the polymer monomer and the metal salt is added dropwise to the mixed solution in step S1 to react (initiating rapid self-polymerization of dopamine into polydopamine, and at the same time, polydopamine and metal ions undergo in-situ coordination reaction); wherein the reaction temperature is 25° C., the reaction time is 24 hours, and a polydopamine-copper polymer precursor is prepared, which is marked as PDA-Cu-C100 polymer precursor;
[0194] S3, collecting the PDA-Cu-C100 polymer precursor in step S2 by centrifugation, transferring it to a vacuum drying oven, and vacuum drying it at 60° C.;
[0195] S4, mixing the PDA-Cu-C100 polymer precursor dried in step S3 with dicyandiamide powder in a mass ratio of 1:11 and grinding for 10 minutes to obtain a uniformly ground powder, which is labeled as PDA-Cu-C100-DCD; then transferring 0.3 g of the uniformly ground PDA-Cu-C100-DCD powder to a quartz boat;
[0196] S5. Transfer the quartz boat carrying PDA-Cu-C80-DCD powder to a tubular furnace for heating pyrolysis treatment; the pyrolysis treatment is specifically as follows: in an argon atmosphere (during the entire pyrolysis process, argon gas with a flow rate of 50 sccm is introduced into the tubular furnace), maintain a constant temperature at 25°C for 1 hour, then increase the temperature from 25°C to 800°C at a rate of 5°C / min, then keep it at 800°C for 1.5 hours, and finally cool naturally to room temperature (25°C); the sample obtained after pyrolysis is a Cu single-atom catalyst, marked as CuNC3.
[0197] This comparative example also provides a method for preparing a gas diffusion electrode, comprising the following steps:
[0198] The CuNC3 prepared in Comparative Example 3 and 100 μL Nafion solution (concentration of 5 wt%) were added to 1 mL of isopropanol and ultrasonicated for 15 min to obtain a catalyst slurry; the catalyst slurry was drop-coated on the surface of the carbon-based gas diffusion layer and dried to obtain a catalyst loading of 0.5 mg / cm 2 The gas diffusion electrode is labeled as CuNC3 / GDL gas diffusion electrode.
[0199] Comparative Example 4
[0200] This comparative example provides a metal-based single-atom catalyst with adjustable site density, comprising the following steps:
[0201] S1. Mix and stir 1 mL of aqueous ammonia (mass concentration of 30%, mass of 0.892 g), 20 mL of ethanol (mass of 15.786 g), and 45 mL of water (mass of 45 g) to obtain a mixed solution;
[0202] S2, adding 0.125g dopamine hydrochloride powder and 0.08g anhydrous copper sulfate powder to 5mL water (mass 5g), stirring and mixing to obtain a mixed solution containing polymer monomers and metal salts;
[0203] The mixed solution containing the polymer monomer and the metal salt is added dropwise to the mixed solution in step S1 to react (initiating rapid self-polymerization of dopamine into polydopamine, and at the same time, polydopamine and metal ions undergo in-situ coordination reaction); wherein the reaction temperature is 25° C., the reaction time is 24 hours, and a polydopamine-copper polymer precursor is prepared, which is marked as PDA-Cu-C160 polymer precursor;
[0204] S3, collecting the PDA-Cu-C160 polymer precursor in step S2 by centrifugation, transferring it to a vacuum drying oven, and vacuum drying it at 60° C.;
[0205] S4, the PDA-Cu-C160 polymer precursor dried in step S3 and the dicyandiamide powder were mixed in a mass ratio of 1:11 and ground for 10 minutes to obtain a uniformly ground powder, which was labeled as PDA-Cu-C160-DCD; then 0.3 g of the uniformly ground PDA-Cu-C160-DCD powder was transferred to a quartz boat;
[0206] S5. Transfer the quartz boat carrying PDA-Cu-C160-DCD powder to a tubular furnace for heating pyrolysis treatment; the pyrolysis treatment is specifically as follows: in an argon atmosphere (during the entire pyrolysis process, argon gas with a flow rate of 50 sccm is introduced into the tubular furnace), maintain a constant temperature at 25°C for 1 hour, then increase the temperature from 25°C to 800°C at a rate of 5°C / min, then keep it at 800°C for 1.5 hours, and finally cool naturally to room temperature (25°C); the sample obtained after pyrolysis is a Cu single-atom catalyst, marked as CuNC4.
[0207] This comparative example also provides a method for preparing a gas diffusion electrode, comprising the following steps:
[0208] The CuNC4 prepared in Comparative Example 4 and 100 μL Nafion solution (concentration of 5 wt%) were added to 1 mL of isopropanol and ultrasonicated for 15 min to obtain a catalyst slurry; the catalyst slurry was drop-coated on the surface of the carbon-based gas diffusion layer and dried to obtain a catalyst loading of 0.5 mg / cm 2 The gas diffusion electrode is labeled as CuNC4 / GDL gas diffusion electrode.
[0209] Characterization of copper single atom catalyst performance
[0210] Statistical results of site density and site spacing of copper single atom catalysts
[0211] Figure 2 In ad, spherical aberration scanning transmission electron micrographs of CuNG1, CuNG2, CuNG3, and CuNG4 copper single atom catalysts prepared in Examples 1 to 4 are shown, and eh is spherical aberration scanning transmission electron micrographs of CuNC1, CuNC2, CuNC3, and CuNC4 copper single atom catalysts prepared in Comparative Examples 1 to 4. The white dots in the white circles represent Cu single atom sites.
[0212] from Figure 2 It can be seen that the site distribution of CuNC series single atoms (ad) is relatively similar, while the site distribution of CuNG series single atoms (eh) shows an obvious gradient densification with the increase of CuSO4 concentration. This shows that the introduction of high-stability support strategy can regulate the site distribution characteristics of Cu single atom catalysts.
[0213] Figure 3 d is the site spacing d of the CuNG1, CuNG2, CuNG3, CuNG4, CuNC1, CuNC2, CuNC3, and CuNC4 copper single atom catalysts prepared in Examples 1 to 4 and Comparative Examples 1 to 4 site value.
[0214] Figure 3 The inter-site spacing results in are statistical averages obtained from Gaussian fits.
[0215] from Figure 3 It can be seen that the inter-site spacing of the CuNG series single atoms obtained in Examples 1 to 4 significantly decreases with the increase of CuSO4 concentration, while the inter-site spacing of the CuNC series single atoms synthesized in Comparative Examples 1 to 4 does not change significantly. This shows that the introduction of a high-stability support strategy can significantly adjust the inter-site spacing of Cu single-atom catalysts.
[0216] Figure 4 is the site density n of the copper single atom catalysts CuNG1, CuNG2, CuNG3, CuNG4, CuNC1, CuNC2, CuNC3, and CuNC4 prepared in Examples 1 to 4 and Comparative Examples 1 to 4 s (Cu atom 100nm -2 ). s represent Figure 2 The area of the scanning transmission electron microscope image is 100nm -2 The total number of Cu single-atom sites in .
[0217] from Figure 4It can be seen that the site density of the CuNG series single atoms obtained in Examples 1 to 4 increases significantly with the increase of CuSO4 concentration, while the site density of the CuNC series single atoms synthesized in Comparative Examples 1 to 4 does not change significantly. This shows that the introduction of a high-stability support strategy can significantly adjust the site density of Cu single-atom catalysts.
[0218] Composite electrode performance test
[0219] The performance of the metal single atom catalyst-diffusion gas diffusion layer composite electrode of Examples 1 to 4 of the present invention and Comparative Examples 1 to 4 was evaluated by using a gas phase diffusion electrolytic cell as a CO2 catalytic reduction reaction device. The specific measurement conditions are as follows:
[0220] CH4 was detected by online gas chromatography (GC2014, Shimadzu, Japan) with a sampling interval of 40 min.
[0221] Gas phase diffusion electrolytic cell CO2 electroreduction performance test:
[0222] (1) Reference electrode: mercury-mercury oxide (1M) electrode;
[0223] (2) Counter electrode: nickel sheet electrode;
[0224] (3) Working electrode: gas diffusion electrode (1×1 cm) prepared in Examples 1 to 4 and Comparative Examples 1 to 4 2 );
[0225] (4) Electrolyte: 1 M KOH solution;
[0226] (5) Ion exchange membrane: Fumasep FAA-3-PK-130;
[0227] (6) CO2 flow rate: 15 sccm
[0228] Faraday efficiency (FE) calculation:
[0229] For gaseous products, a gas chromatograph is used for quantitative analysis, and the Faraday efficiency calculation formula is: in:
[0230] In the formula, z is the number of transferred electrons; F is the Faraday constant (96485C·mo1 -1 );C i is the concentration of the product (ppm×10 -6 ); v is the gas flow rate into the chromatogram (m 3 ·s -1 ); P is the pressure of the chromatographic injection loop (Pa); j is the current density (A); R is the ideal gas constant (8.314 J·mol -1 ·K-1 );T is the temperature of the chromatographic injection loop (K).
[0231] According to the above method, the Faraday efficiency of the gas diffusion electrodes prepared in Examples 1 to 4 and Comparative Examples 1 to 4 for catalytic reduction to produce CH4 at different potentials was tested. The results are as follows: Figure 5 shown.
[0232] in, Figure 5 In a, a Faraday efficiency diagram of the gas diffusion electrodes prepared in Examples 1 to 4 for catalytic reduction to produce CH4 at different potentials, and in b, a Faraday efficiency diagram of the gas diffusion electrodes prepared in Comparative Examples 1 to 4 for catalytic reduction to produce CH4 at different potentials.
[0233] Figure 5 CuNG1 / GDL, CuNG2 / GDL, CuNG3 / GDL, and CuNG4 / GDL respectively represent the gas diffusion electrodes prepared in Examples 1 to 4; CuNC1 / GDL, CuNC2 / GDL, CuNC3 / GDL, and CuNC4 / GDL respectively represent the gas diffusion electrodes prepared in Comparative Examples 1 to 4.
[0234] from Figure 5 It can be seen that the Faraday efficiency of the gas diffusion electrodes prepared in Examples 1 to 4 and Comparative Examples 1 to 4 for reducing CH4 at different potentials is shown in Tables 1 to 8. In Tables 1 to 8, RHE is a reversible hydrogen electrode.
[0235] The electrocatalytic performance of the gas diffusion electrode CuNG1 / GDL prepared in Example 1 at different potentials is shown in Table 1 below.
[0236] Table 1-Electrocatalytic performance of CuNG1 / GDL at different potentials
[0237] Potential / V(versus RHE) -0.4 -0.6 -0.8 -1.0 -1.2 <![CDATA[CH4 Faraday efficiency / %]]> >4.6 >11.3 >21.2 >30.3 >29.4
[0238] The electrocatalytic performance of the gas diffusion electrode CuNG2 / GDL prepared in Example 2 at different potentials is shown in Table 2 below.
[0239] Table 2-Electrocatalytic performance of CuNG2 / GDL at different potentials
[0240]
[0241]
[0242] The electrocatalytic performance of the gas diffusion electrode CuNG3 / GDL prepared in Example 3 at different potentials is shown in Table 3 below.
[0243] Table 3-Electrocatalytic performance of CuNG3 / GDL at different potentials
[0244] Potential / V(versus RHE) -0.5 -0.7 -0.8 -1.0 -1.3 -1.4 <![CDATA[CH4 Faraday efficiency / %]]> >29.8 >61.3 >66.2 >70.0 >61.7 >57.6
[0245] The electrocatalytic performance of the gas diffusion electrode CuNG4 / GDL prepared in Example 4 at different potentials is shown in Table 4 below.
[0246] Table 4-Electrocatalytic performance of CuNG4 / GDL at different potentials
[0247] Potential / V(versus RHE) -0.5 -0.6 -0.7 -1.0 -1.3 <![CDATA[CH4 Faraday efficiency / %]]> >6.0 >33.9 >45.5 >51.0 >49.8
[0248] The electrocatalytic performance of the gas diffusion electrode CuNC1 / GDL prepared in Comparative Example 1 at different potentials is shown in Table 5 below.
[0249] Table 5-Electrocatalytic performance of CuNC1 / GDL at different potentials
[0250] Potential / V(versus RHE) -0.6 -0.7 -0.8 -0.9 -1.1 -1.4 <![CDATA[CH4 Faraday efficiency / %]]> >35.5 >55.6 >55.5 >55.3 >49.0 >36.2
[0251] The electrocatalytic performance of the gas diffusion electrode CuNC2 / GDL prepared in Comparative Example 2 at different potentials is shown in Table 6 below.
[0252] Table 6-Electrocatalytic performance of CuNC2 / GDL at different potentials
[0253] Potential / V(versus RHE) -0.5 -0.6 -0.7 -0.8 -1.0 -1.4 <![CDATA[CH4 Faraday efficiency / %]]> >32.2 >54.7 >58.1 >55.5 >53 >39.3
[0254] The electrocatalytic performance of the gas diffusion electrode CuNC3 / GDL prepared in Comparative Example 3 at different potentials is shown in Table 7 below.
[0255] Table 7-Electrocatalytic performance of CuNC3 / GDL at different potentials
[0256] Potential / V(versus RHE) -0.5 -0.7 -0.8 -1.0 -1.4 <![CDATA[CH4 Faraday efficiency / %]]> >29.4 >54.1 >57.8 >52.6 >40.6
[0257] The electrocatalytic performance of the gas diffusion electrode CuNC4 / GDL prepared in Comparative Example 4 at different potentials is shown in Table 8 below.
[0258] Table 8-Electrocatalytic performance of CuNC4 / GDL at different potentials
[0259] Potential / V(versus RHE) -0.5 -0.6 -0.7 -0.8 -0.9 -1.3 <![CDATA[CH4 Faraday efficiency / %]]> >12.1 >35.5 >50.8 >55.7 >51.2 >38.1
[0260] Depend on Figure 5 It can be seen that when the gas diffusion electrodes (Cu single atom catalyst-diffusion gas diffusion layer composite electrodes) prepared in Examples 1 to 4 of the present invention are used in the electrocatalytic CO2 to CH4 process, the selectivity of the reaction of the Cu single atom catalyst containing a thermally stable carrier is adjustable, and is greatly improved compared to the catalysts without a thermally stable carrier in Comparative Examples 1 to 4.
[0261] It can be understood that the technical features of the above-described embodiments can be arbitrarily combined. In order to make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0262] The above are only preferred embodiments of the present application, and only specifically describe the technical principles of the present application. These descriptions are only for explaining the principles of the present application and cannot be interpreted as limiting the scope of protection of the present application in any way. Based on the explanation here, any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application, and other specific implementation methods of the present application that can be associated with the technicians in this field without creative work, should be included in the scope of protection of the present application.
Claims
1. A metal-based single-atom catalyst with adjustable site density, characterized in that: A heteroatom hybridized support and a metal, wherein the metal is supported on the support at a single atom site; The metal is coordinated to at least one of the heteroatoms; The carrier is a carrier with high thermal stability, and the thermal decomposition loss of the carrier at a temperature of 300 to 1200° C. is 0.1 wt % to 90 wt %.
2. The metal-based single-atom catalyst with adjustable site density as claimed in claim 1, characterized in that: The metal includes at least one of copper, cobalt, aluminum, iron, manganese, indium, nickel, tin, silver, palladium, platinum, and gold; And / or, the carrier includes at least one of a metal carrier, a metal oxide carrier, a metal carbide carrier, a metal nitride carrier, a metal phosphide carrier, a metal sulfide carrier, and a carbon carrier; And / or, the heteroatom includes at least one of carbon, nitrogen, oxygen, sulfur, chlorine, and phosphorus.
3. The metal-based single-atom catalyst with adjustable site density as claimed in claim 2, characterized in that: The site density of the metal is 1 to 256 / 25nm 2 ; The metal carrier includes at least one of Pt, Au, Ag, Pd, and Rh; The metal oxide carrier includes at least one of CeO2, Al2O3, Cr2O3, and TiO2; The metal carbide carrier includes at least one of WC, VC, ZrC, TaC, SiC, and B4C; The metal nitride carrier includes at least one of TaN and AlN; The carbon carrier includes at least one of graphite, carbon nanotubes, graphyne, graphene, fullerene, and carbon particles.
4. A method for preparing a metal-based single-atom catalyst with adjustable site density as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: adding the carrier to water and mixing to obtain a suspension; Adding alkaline substances and organic solvents to the suspension, stirring, and obtaining a mixed solution; Adding a mixed solution containing polymer monomers and metal salts into the mixed solution, reacting, separating the solid and the liquid, obtaining a precipitated product, and drying; The dried precipitated product is mixed with carbon and nitrogen compounds and then pyrolyzed in an inert atmosphere to obtain a metal-based single-atom catalyst with adjustable site density; The carrier is a carrier with high thermal stability, and the thermal decomposition loss of the carrier at a temperature of 300 to 1200° C. is 0.1 wt% to 90 wt%.
5. The method for preparing a metal-based single-atom catalyst with adjustable site density as claimed in claim 4, characterized in that: Before adding the carrier into the water, the method further includes adding an organic solvent into the water, wherein the volume ratio of the organic solvent to water is (1-100):(1-3).
6. The method for preparing a metal-based single-atom catalyst with adjustable site density as claimed in claim 5, characterized in that: The alkaline substance includes at least one of ammonia solution, sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, sodium hydroxide solution, potassium hydroxide solution, calcium hydroxide, and barium hydroxide; and / or, the organic solvent comprises at least one of methanol, ethanol, glycerol, acetonitrile, acetone, chloroform, pyridine, N-methylpyrrolidone, and dimethylformamide; And / or, the polymer monomer includes at least one of aniline monomers, pyrrole monomers, thiophene monomers, indole monomers, pyridine monomers, carbazole monomers, dopamine monomers, and p-phenylene vinylene monomers; And / or, the metal salt includes at least one of a metal sulfate, a metal nitrate, a metal hypochlorite, a metal chlorate, a metal perchlorate, a metal fluoride, a metal acetate, a metal trifluoroacetate, a metal trifluoromethanesulfonate, a metal methanesulfonate, a metal p-toluenesulfonate, and a metal chloride; The metal in the metal salt includes at least one of copper, cobalt, aluminum, iron, manganese, indium, nickel, tin, silver, palladium, platinum and gold; And / or, the carbon-nitrogen compound includes at least one of urea, dicyandiamide, melamine, thiourea and amino acid.
7. The method for preparing a metal-based single-atom catalyst with adjustable site density as claimed in claim 4, characterized in that: The pyrolysis temperature is 300-1200° C. and the time is 0.1-72 hours.
8. The method for preparing a metal-based single-atom catalyst with adjustable site density as claimed in claim 4, characterized in that: The concentration of the metal salt in the mixed solution containing the polymer monomer and the metal salt is 0.1 to 10 mg / mL; and / or, the concentration of the polymer monomer in the mixed solution containing the polymer monomer and the metal salt is 10 to 30 mg / mL; And / or, in the step of mixing the dried precipitated product with the carbon and nitrogen compound, the mass ratio of the dried precipitated product to the carbon and nitrogen compound is 1:(1-100).
9. The method for preparing a metal-based single-atom catalyst with adjustable site density according to claim 7, characterized in that: The pyrolysis comprises: mixing the dried precipitation product with the carbon and nitrogen compound in an inert atmosphere, firstly keeping the temperature at 0-40°C for 0.5-1h, then heating to 300-1200°C at a rate of 1-50°C / min and keeping the temperature for 0.1-72h. The inert atmosphere environment is an environment filled with inert gas, and the inert gas includes at least one of nitrogen, helium, neon, argon, krypton, and xenon.
10. The method for preparing a metal-based single-atom catalyst with adjustable site density according to claim 4, characterized in that: A mixed solution containing polymer monomers and metal salts is added to the mixed solution. In the reaction step, the reaction temperature is 20 to 30° C. and the reaction time is 20 to 30 hours.
11. The method for preparing a metal-based single-atom catalyst with adjustable site density according to any one of claims 5 to 10, characterized in that: The following steps are involved: Adding a carrier and an organic solvent into water and mixing them to obtain a suspension; Adding alkaline substances and organic solvents to the suspension, stirring, and obtaining a mixed solution; Adding a mixed solution containing polymer monomers and metal salts into the mixed solution, reacting, separating the solid and the liquid, obtaining a precipitated product, and drying; The dried precipitated product is mixed with carbon and nitrogen compounds and then pyrolyzed in an inert atmosphere to obtain a metal-based single-atom catalyst with adjustable site density; Wherein, the carrier is a graphite sheet, the metal salt is a copper salt, the polymer monomer is dopamine hydrochloride, and the alkaline substance is ammonia water; the mass concentration of the ammonia water is 25-32%; The mixed solution is prepared by adding dopamine hydrochloride and copper salt into water to obtain a mixed solution; In the step of adding a carrier and a first organic solvent to water, the mass ratio of the carrier, the organic solvent and the water is (0.05-0.2):(3-7):(40-50); In the step of adding an alkaline substance and an organic solvent to the suspension, the mass ratio of the alkaline substance to the first organic solvent is (0.88-0.92):(14-18); In the step of adding dopamine hydrochloride and copper salt to water, the mass ratio of dopamine hydrochloride, copper salt and water is (0.1-0.3):(0.02-0.08):(3-7); The mass ratio of the carrier, the alkaline substance and dopamine hydrochloride is (0.05-0.2):(0.88-0.92):(0.1-0.3).
12. A gas diffusion electrode, characterized in that: It comprises a substrate and a catalyst loaded on the substrate, wherein the catalyst is a metal-based single-atom catalyst with adjustable site density as described in any one of claims 1 to 3 or a metal-based single-atom catalyst with adjustable site density prepared by the preparation method as described in any one of claims 4 to 11.
13. Use of a metal-based single-atom catalyst with adjustable site density as described in any one of claims 1 to 3, or a metal-based single-atom catalyst with adjustable site density prepared by the preparation method described in any one of claims 4 to 11, or a gas diffusion electrode described in claim 12 in CO2 electrocatalytic reduction reaction.
Citation Information
Patent Citations
Nitrogen-doped porous carbon-loaded monatomic catalyst as well as preparation method and application thereof
CN116885215A
Metal monatomic catalyst, preparation method and application
CN117884158A
Gradient-size magnetoelectric heterostructure and preparation method and application thereof
CN120035109A